A Penta- and Hexa-Coordinated Trinuclear Nickel(II) Complex [(NiL)2(OAc)2Ni]·2(n-PrOH)·CHCl3: Synthesis and Crystal Structure - Sun, Yin-Xia; Zhang, Yu-Jie; Dong, Xiu-Yan; Li, Xin-Ran; Meng, Wei-Sheng; Lu, Rui-E (Asian Journal of Chemistry, 2013)
A tri-nuclear Ni(II) complex, [(NiL)2(OAc)2Ni]·2(n-PrOH)·CHCl3, has been synthesized by the reaction of Ni(II) acetate tetrahydrate with a salen-type bisoxime chelating ligand (H2L). The X-ray crystal structure of the complex reveals that there are two acetate ions coordinate to three Ni(II) atoms through Ni-O-C-O-Ni bridges and quadruple μ-phenoxo oxygen atoms from two [NiL] chelates also coordinate to Ni(II) atoms. Interestingly, the Ni(II) complex possessing different conformational metal centers: penta- and hexa-coordinated geometry.